Bokashi compost and biofertilizer increase lettuce agronomic variables in protected cultivation and indicates substrate microbiological changes - Hata, Fernando Teruhiko; Spagnuolob, Felipe Alvares; Paulaa, Maria Tereza de; Moreiraa, Amanda Aleixo; Venturaa, Mauricio Ursi; Fregonezic, Gustavo Adolfo de Freitas; Oliveiraa, André Luiz Martinez de (Emirates Journal of Food and Agriculture, 2020)
The aim of the study was to evaluate agronomic productive variables of iceberg lettuce and soil microbiological variables for two crop cycles by using organic inputs. The treatments were as follows: control (no fertilization); Bokashi compost (20 g per plant); Penergetic-k plus Penergetic-p bio-activators (both at 1.5 g per litre of water, applied to the substrate and plant, respectively); and biofertilizer at different concentrations (2.5, 5.0, 7.5, and 10% dilutions in water). Biofertilizer concentrations were applied during five fertigation times per day in the first crop experiment and in single daily fertigation in the second crop experiment. Agronomic productive variables evaluated were: total mass, commercial mass, discarded leaves mass, stem diameter, commercial head diameter and plant height. Soil microbial biomass carbon, basal soil respiration and metabolic quotient were evaluated for substrate microbial quality measurement. In the first cycle, plants treated with Bokashi or Penergetic presented superior total mass, commercial mass and commercial head diameter of lettuce, while plants treated with biofertilizer did not exhibit improvement and presented tipburn in some plants, when compared to control. In the second cycle, the use of Bokashi and biofertilizers improved the total mass and commercial head diameter, compared to control. Higher than control microbial biomass was achieved with biofertilizer concentrations and Bokashi. Lower metabolic quotient (qCO2) was observed for all the treatments, when compared to control. Soil microbial quality data corresponded to better lettuce yields.